A checklist of the Eurytomidae (Hymenoptera, Chalcidoidea) species of Turkey - Çam Hali̇t (Zootaxa, 2011)
A checklist of 87 species in 9 genera belonging to 2 subfamilies (Eurytominae and Rileyinae) of Eurytomidae (Hymenoptera: Chalcidoidea) known from Turkey is presented. Host or collection information and distributional data in Turkey are also provided.